Evaluasi Sumber Daya Teknologi Informasi pada Pusat Data dan Sarana Informatika Kementrian Komunikasi dan Informatika Republik Indonesia Menggunakan Kerangka Kerja COBIT 5 Sub Domain EDM 04, APO 07, dan DSS 02 - Rafael George; Suprapto Suprapto; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The Ministry of Communication and Information Technology in Indonesia is a government organizers in the field of communication and information technology. The success of the ministry on doing its job is based on the existence of information technolgy. Data Center and information Facilities troops is responsible for information technology management. The importance of managing information technology is aligned with managing of optimal information technology resources to support business activities. With the obstacles that have been found about information technology resources currently, human resources management, service request and incindents on Data Center and Information Facilities troops, therefore it's necessary to do the evaluation focus on the problems to help providing recomendations for fixing and improving the problems. The COBIT 5 framework is appropriate to evaluate information technology resources on subdomain EDM04: Ensure Resource Optimisation, APO07: Manage Human Resources, and DSS02: Manage Service Request and Incidents to determine capability level and GAP analysis. The result of capability level on EDM04 and APO07 is at the level 3, DSS02 is at the level 2 with the value of each subdomain gap score 1. In hope that the organization can achieve the targeted level, the recommendation given is focusing on control in each procedures, defining organization structure, and truning systematic documents in incidents handling and service request.